Makna Pemanfaatan Hijab dalam Iklan Produk Shampo Versi Berjilbab di Televisi - Alfia Zain; Fatmawati Sofyan (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
This study aims to determine the meaning of the use of hijab to the beauty of women’s hair contained in Sunsilk Clean And Fresh product ads on television using Charles Sanders Peirce’s semiotic analysis model. This research uses qualitative approach with descriptive method of analysis, and constructivist paradigm. Data collection techniques used were observations by observing Sunsilk Clean And Fresh advertisements, interviews with related informants, and documentation. The results of this study found that ad in Shampo Sunsilk Clean and Fresh products describes the comfort and freshness of a woman’s hair that uses hijab throughout the day by performing a dense activity. The meaning contained in this ad corresponds to Charles Sanders Peirce’s semiotic model. Then, the use of veils from advertising ultimately leads to controversy in a person, society and social environment. The meaning of hijab as a Muslim identity is utilized in advertising as a commercial medium that obscures the purpose of the hijab user themselves.